Cotidianidad en el manejo del estado financiero de familias cuidadoras del paciente con cáncer terminal - Pacasmayo 2015 - Castañeda Nomberto, Vilma Elizabeth (2015)
Qualitative descriptive study aimed at describing and analyzing the everyday in managing the financial status of family carers of a member with terminal cancer. The research took the city of Pacasmayo (Peru). Semistructured interview five families was applied, of which 2 was high economic level and 3 low economic level. The thematic content analysis was used, coming to get three main categories, as first category: managing the financial status of family carers of patients with terminal cancer, result in turn the following thematic units: management of the financial status of family carers, and care of patients with terminal cancer. The second category called financial management to the health care of the family and patient care. The third category differences in the care they provide families based management financial statement for the family member suffering from terminal cancer. She had the final considerations that everyday in managing the financial status of family carers of patients with terminal cancer is based entirely on the sick relative, and depends on the economic situation of each family, ie revenues are there Family, are designed to meet the needs of the patient; by relating it to the health care of the family, an oversight is evident in meeting the needs of this, especially in low-income families, which is created by the need to build new income and provide better quality of life to the sick relative